Technology in Microclimate Control for Industrial Buildings: Enhancing Efficiency and Comfort - I.F.N Dotsent Sabirov Ulug‘bek Kuchkarovich; Oqilov Azizbek Kozimjon o‘g‘li (Zien Journals, 2023)
This article provides a comprehensive literature review on the topic of microclimate control in industrial buildings. It explores the challenges associated with controlling the microclimate in such structures, including temperature extremes, humidity management, and ventilation issues. The review highlights various innovative solutions and techniques for effective microclimate control, such as highefficiency HVAC systems, automation and smart systems, sustainable design strategies, and renewable energy integration. The article emphasizes the benefits of enhanced microclimate control, including increased productivity, improved energy efficiency, and better health and safety conditions. The review concludes by emphasizing the importance of continued research and collaboration in the field to further advance microclimate control in industrial buildings.
Keywords: productivity; energy consumption; working environment; smart systems